Exclusively endoscopic surgical resection of esthesioneuroblastoma: A systematic review. Issue 1 (22nd March 2022) - Spielman, Daniel B.; Liebowitz, Andi; Grewal, Maeher; Safi, Chetan; Overdevest, Jonathan B.; Iloreta, Alfred M.; Youngerman, Brett E.; Gudis, David A.
Abstract: Background: Historically sinonasal malignancies were always addressed via open craniofacial surgery for an oncologic resection. Increasingly esthesioneuroblastomas are excised using an exclusively endoscopic approach, however, the rarity of this disease limits the availability of long‐term and large scale outcomes data. Objective: The primary objective is to evaluate the treatment modalities used and the overall survival of patients with esthesioneuroblastoma managed with exclusively endoscopic surgery. Methods: In accordance with PRISMA guidelines, PubMed was queried to identify studies describing outcomes associated with endoscopic management of esthesioneuroblastomas. Results: Forty‐four out of 2462 articles met inclusion criteria, totaling 399 patients with esthesioneuroblastoma treated with an exclusively endoscopic approach. Seventy‐two patients (18.0%) received adjuvant chemotherapy and 331 patients (83.0%) received postoperative radiation therapy. The average age was 50.6 years old (range 6–83). Of the 399 patients, 57 (16.6%) were Kadish stage A, 121 (35.2%) were Kadish stage B, 145 (42.2%) were Kadish stage C, and 21 (6.1%) were Kadish stage D. Pooled analysis demonstrated that 66.0% of patients had Hyams histologic Grade Ⅰ or Ⅱ, while 34.0% of patients had Grade Ⅲ or Ⅳ disease. Negative surgical margins were achieved in 86.9% of patients, and recurrence was identified in 10.3% of patients. Of those with 5‐year follow‐up, reported overall survival was 91.1%. Conclusion: Exclusively endoscopic surgery for esthesioneuroblastoma is performed for a wide range of disease stages and grades, and the majority of these patients are also treated with adjuvant chemotherapy or radiation therapy. Reported overall recurrence rate is 10.3% and 5‐year survival is 91.1%. Abstract : Exclusively endoscopic surgery for esthesioneuroblastoma is performed for a wide range of disease stages and grades with minimal associated morbidity and low complication rates. The majority of these patients are also treated with adjuvant chemotherapy or radiation therapy.